A compendium answering 150 questions on COVID‐19 and SARS‐CoV‐2. Issue 10 (20th July 2020) - Riggioni, Carmen; Comberiati, Pasquale; Giovannini, Mattia; Agache, Ioana; Akdis, Mübeccel; Alves‐Correia, Magna; Antó, Josep M.; Arcolaci, Alessandra; Azkur, Ahmet Kursat; Azkur, Dilek; Beken, Burcin; Boccabella, Cristina; et al.
Abstract: In December 2019, China reported the first cases of the coronavirus disease 2019 (COVID‐19). This disease, caused by the severe acute respiratory syndrome–related coronavirus 2 (SARS‐CoV‐2), has developed into a pandemic. To date, it has resulted in 9 million confirmed cases and caused almost 500 000 related deaths worldwide. Unequivocally, the COVID‐19 pandemic is the gravest health and socioeconomic crisis of our time. In this context, numerous questions have emerged in demand of basic scientific information and evidence‐based medical advice on SARS‐CoV‐2 and COVID‐19. Although the majority of the patients show a very mild, self‐limiting viral respiratory disease, many clinical manifestations in severe patients are unique to COVID‐19, such as severe lymphopenia and eosinopenia, extensive pneumonia, a "cytokine storm" leading to acute respiratory distress syndrome, endothelitis, thromboembolic complications, and multiorgan failure. The epidemiologic features of COVID‐19 are distinctive and have changed throughout the pandemic. Vaccine and drug development studies and clinical trials are rapidly growing at an unprecedented speed. However, basic and clinical research on COVID‐19–related topics should be based on more coordinated high‐quality studies. This paper answers pressing questions, formulated by young clinicians and scientists, on SARS‐CoV‐2, COVID‐19, and allergy, focusing on the following topics: virology, immunology, diagnosis, management of patients with allergic disease and asthma, treatment, clinical trials, drug discovery, vaccine development, and epidemiology. A total of 150 questions were answered by experts in the field providing a comprehensive and practical overview of COVID‐19 and allergic disease.